INTERCELLULAR AND CELL-MATRIX INTERACTIONS IN BREAST CARCINOMA: THE PRESENT STATE OF PROBLEM - M. V. Mnikhovich; E. S. Mishinа; T. В. Bezuglova; K. V. Bun’kov (Опухоли женской репродуктивной системы, 2018)
In the article, based on the analysis of literature and own data, the study of intercellular and cell-matrix interactions in breast tumors was performed. The data considered in the article are important for understanding the processes of intercellular interaction and patterns of tumor growth, since tumor microenvironment plays an important role in the regulation of tumor state.